2022
DOI: 10.1080/21505594.2022.2112818
|View full text |Cite
|
Sign up to set email alerts
|

Role of aggregate-forming pilus (AFP) in adherence and colonization of both intestinal and urinary tracts

Abstract: Hybrid-pathogenic Escherichia coli represent an important group of strains associated with intestinal and extraintestinal infections. Recently, we described strain UPEC-46, a uropathogenic/enteroaggregative E. coli (UPEC/EAEC) strain presenting the aggregative adherence (AA) pattern on bladder and colorectal epithelial cells mediated by aggregate-forming pili (AFP). However, the role of AFP and other uninvestigated putative fimbriae operons in UPEC-46 pathogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…EAEC is recognized as an important cause of diarrhoea worldwide and can be considered the most common DEC pathotype in E. coli in Brazil. However, E. coli strains with a hybrid enteroaggregative/uropathogenic (UPEC/EAEC) genotype have sporadically emerged as a cause of extraintestinal infections in Brazil [10][11][12][13][14][15][16][17][18]. Here we demonstrated the high prevalence of such hybrid pathotypes in distinct lineages causing infections in the Amazon region.…”
Section: Resultsmentioning
confidence: 83%
“…EAEC is recognized as an important cause of diarrhoea worldwide and can be considered the most common DEC pathotype in E. coli in Brazil. However, E. coli strains with a hybrid enteroaggregative/uropathogenic (UPEC/EAEC) genotype have sporadically emerged as a cause of extraintestinal infections in Brazil [10][11][12][13][14][15][16][17][18]. Here we demonstrated the high prevalence of such hybrid pathotypes in distinct lineages causing infections in the Amazon region.…”
Section: Resultsmentioning
confidence: 83%
“…Aggregate-forming pili (AFP) and type I mbriae (TIF) have synergistic effects on the adhesion and colonization of intestinal and urinary epithelial cells; therefore, mixed E. coli strains possessing AFP and TIF may infect both the intestinal and urinary tracts and are therefore more di cult to treat. [43] However, whether testosterone can be used as an anti-infective agent for defending UPEC to continuously infect prostate epithelial cells, especially against strains with strong virulence factors, such as FimH, remains to be further studied. In conclusion, our study indicates that testosterone can be used to treat clinical recurrent UPEC infection and persistent prostatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Also important to note that 100% of these 74 AAF+ strains were aggR + and presented AA pattern in HeLa cells adherence assays, while 100% of AFP+ strains were aggR- . While the role of AAF in pathogenesis and as a specific EAEC marker is well stablished, recent data showed that AFP has emerged as an important virulence trait in a subset of EAEC strains carrying aat , aai and aap ( Lang et al., 2018 ; Dias et al., 2020 ; Schüroff et al., 2021 ; Schüroff et al., 2022 ). Considering our results, and the EAEC classification proposed by Kaper et al.…”
Section: Discussionmentioning
confidence: 99%
“…This plasmid (pAFP) also carried a new adhesin named aggregative-forming pilus (AFP) encoded by the afp operon, which among its components carries an AraC-like regulator very similar to aggR , named afpR . AFP was shown to be involved in bacterial piliation, autoaggregation, adhesion and cytotoxicity ( Lang et al., 2018 ) and was recently observed mediating AA in a hybrid enteroaggregative/uropathogenic E. coli (EAEC/UPEC) strain ( Schüroff et al., 2021 ; Schüroff et al., 2022 ). Moreover, phylogenetic analyses have shown that AFP-positive strains carrying other virulence genes related to EAEC pathogenesis ( aat operon, type 6 secretion system genes and aap ), are clustered with other fecal EAEC strains ( Schüroff et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%